The red cell distribution width (RDW): Value and role in preterm, IUGR (intrauterine growth restricted), full-term infants. Issue 6 (September 2014) - Garofoli, Francesca; Ciardelli, Laura; Mazzucchelli, Iolanda; Borghesi, Alessandro; Angelini, Micol; Bollani, Lina; Genini, Emilia; Manzoni, Paolo; Paolillo, Piermichele; Tinelli, Carmine; Merlini, Giampaolo; Stronati, Mauro
Abstract : Objective: To measure the red cell distribution width (RDW) ranges at birth and to evaluate potential association with typical neonatal diseases: patent of the ductus arteriousus (PDA), bronchopulmonary dysplasia (BPD), and late-onset sepsis (LOS) mortality. Methods: Forty-six full-term, 41 preterm, and 35 intrauterine growth restricted (IUGR) infants participated in this retrospective, observational study. RDW was measured before 3 days of life (T0) in all infants, and at first month of life (T1) in preterm/IURG patients. Results: RDW% mean (standard deviation) at T0 was: 15.65 (1.18) in full-term newborns; 17.7 (2.06) in preterm; 17.45 (1.81) in IUGR. A negative correlation ( r  = −0.51; P  < 0.001) between RDW and gestational age was found. RDW at T1 was: 17.25 (2.19) in the preterm group; 17.37 (2.56) in IUGR group. Fourteen preterm infants reported: 12 PDA, 5 LOS, 4 BPD, and 3 died; 10 IUGR infants had: 4 PDA, 6 LOS, 3 BPD, and 1 died. RDW of IUGR infants suffering from those pathologies was not statistically different compared with unaffected infants, while preterm newborns with pathologies reported higher RDW: PDA vs. PDA absent: P  = 0.008 at T0; P  < 0.002 at T1. BPD vs. BPD absent: P  < 0.005 at T1. LOS vs. LOS absent: P  < 0.005 at T0. RDW in preterm/IUGR population was associated with early mortality, T0: dead 21.2 (2.7) vs. alive 16.7 (1.7), P  < 0.0001. Conclusion: RDW and gestational age at birth were negatively correlated. High RDW resulted to be an indication of risk for critical newborns. This parameter can be inexpensively and routinely verified and further studies are required to confirm its prognostic role in neonatal pathologies.